2001
DOI: 10.1207/s15327752jpa7703_13
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Beck Depression Inventory-II With University Students in Bahrain

Abstract: The Arabic version of the Beck Depression Inventory-II (BDI-II; Beck, Steer, & Brown, 1996) was administered to 200 students enrolled at the University of Bahrain. Using exploratory and confirmatory factor analytic techniques, I obtained reasonable validity and reliability data for the BDI-II. Three oblique factors provided the most parsimonious and meaningful solution for students' responses. Findings of this study generally provide strong support for the psychometric soundness of the BDI-II as a measure of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 18 publications
6
64
0
1
Order By: Relevance
“…Scores range from 0 to 63, with higher scores indicating more depressive symptoms. Numerous studies have documented the internal consistency, test-retest reliability, and construct validity of the scale in various populations (Al-Musawi, 2001;Coles et al, 2001;Kojima et al, 2002). The BDI-II had an internal consistency Cronbach's α coefficient of 0.92 in the present sample.…”
Section: The Beck Depression Inventory-ii (Bdi-ii)mentioning
confidence: 52%
“…Scores range from 0 to 63, with higher scores indicating more depressive symptoms. Numerous studies have documented the internal consistency, test-retest reliability, and construct validity of the scale in various populations (Al-Musawi, 2001;Coles et al, 2001;Kojima et al, 2002). The BDI-II had an internal consistency Cronbach's α coefficient of 0.92 in the present sample.…”
Section: The Beck Depression Inventory-ii (Bdi-ii)mentioning
confidence: 52%
“…Concurrent validity was evaluated using -Khalek, 1998;Al-Musawi, 2001;Al-Turkait and Ohaeri, 2010) and the CES-D (Ghubash et al, 2000;Kazarian and Taher, 2010) were not selected because they have been validated in college students and community samples, not in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since first developed in 1961, the Beck Depression Inventory (BDI) has been used to assess both the presence and the severity of depressive symptoms around the world. Its revised form known as BDI-II [Beck et al, 1996] has also been translated and validated for many languages and cultures [e.g., Alansari, 2006;Al-Musawi, 2001;Ghassemzadeh et al, 2005;Kojima et al, 2002] and therefore seems to maintain the reputation of its previous versions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been validated in community adolescents [Byrne et al, 2004], community adult or college student samples [Alansari, 2006;Al-Musawi, 2001;Bonicatto et al, 1998;Ghassemzadeh et al, 2005;Gorenstein et al, 1999;Kojima et al, 2002] and clinical samples [Steer et al, 1999;Viljoen et al, 2003]. These studies have examined BDI-II to assess whether its original factor structure suggested by Beck et al [1996] was confirmed in the above-mentioned samples.…”
Section: Introductionmentioning
confidence: 99%